The variation of microcrustaceans diversity downstream of small reservoirs is influenced by litoranean taxa - Sartori, Milena; Martins, Barbara A. [UNESP]; Perbiche-Neves, Gilmar (Fundacao Zoobotanica Rio Grande Sul, Museu Ciencias Naturais, 2021)
The hypotheses tested were that, as well as in reservoirs of large surface areas, volumes and flow, in small reservoirs there is also a gradual and continuous dilution of the richness, diversity and abundance of microcrustaceans (Cladocera and Copepoda) downstream reservoirs, without the recomposition of richness downstream due to the lack of tributary rivers, marginal lagoons and even the small size of the stream, with no conditions for the development of its own potamoplankton. Two small reservoirs were studied and in their downstream stretches, with daily collections every six hours at eight sampling points, two lentic and six lotic downstream from each. Nineteen species were found (11 from Cladocera and eight from Copepoda), with emphasis on the greater number of coastal species than pelagic ones, and the greater abundance of coastal cladocerans at the points downstream of the reservoirs. There was no difference between the times, indicating that the spatial scale was more important than the temporal scale. There were higher values of ecological attributes in lentic environments, but there were significant increases in richness and diversity in the last points of the stretches of the stream, while the abundance decreased gradually downstream. No significant correlations were found for the abundance of taxa with any physical and chemical variable (temperature, pH, dissolved oxygen, turbidity, total dissolved solids and transparency), indicating little or no effect of these variables. The cluster analysis with Euclidean distance separated two large groups, the first formed by the stretch downstream of the first reservoir and the second with the other points. In addition to the presence of litoranean taxa coming from reservoirs, there was an increase in litoranean taxa resident in streams. It can be concluded that there was a dilution of the abundance of species downstream of the streams, but the richness and diversity remained stable due to the contribution of litoranean taxa.
Keywords: Zooplankton; spatial variation; recomposition; flow